Accountability of the Quality and Equity of an Educational Policy: the Case of Preferential School Subsidy for Vulnerable Children in Chile - de la Vega Rodríguez, Luis Felipe; Picazo Verdejo, María Inés (Revista del CLAD Reforma y Democracia, 2016)
A major change in the management of public resources accompanied the political and social concern to improve the quality and equity of education of vulnerable children in Chile. This is expressed in the incorporation of accountability mechanisms in one of the most important policies of the decade in this country: the Preferential School Subsidy (SEP). This document aims at analyzing accountability in that policy, wondering how manages to bring in a balanced way to achieving the objectives of improving educational management, with equity-related aspirations, goals that are deeply demanded by the education system, but at the same time they are in a constant tension in public policy. Accountability in this paper is understood as a system of responsibilities between the actors involved in the operations of the schools. This article described and analyzed the model of change of SEP law and the role of accountability mechanism it uses, associated with the achievement of certain objectives and learning outcomes. Then, a study of eight cases related to schools in different social and educational backgrounds was conducted, by analyzing the extent to which each stakeholder did the responsibilities defined by law. With that information, it was assessed how the actual fulfillment of those responsibilities shows to what extent the SEP is achieving balance the aspirations of improving management, with equity and participation. The results describe the difficulty of combining these goals and show only partial implementation of accountability in the case studies.
Keywords: Accountability; Educational Policy; Quality; Social Equity; Policies Implementation; Public Policy; Chile